THE EPISTEMOLOGY OF BAYANI, BURHANI AND IRFANI 'ABID AL JABIRI AND ITS RELEVANCE IN ISLAMIC EDUCATION - Rasmuin, Mr. (Al Ghazali, 2019)
This paper describes one of the masterpieceof modern Islamic philosophical thought initiated by Muhammad Abid Al Jabiri. He is an Islamic scientist from Morocco who has used the epistemology method as his analytical knife in studying Arabic-Islamic reasoning. This was the topic of his study because he felt that one of the problems of the destruction of thought, ambiguity and doubt in understanding the knowledge experienced by humans, was a result of epistemological errors. In this paper, we will explain how the epistemology built by Al-Jabiri and its tendency towards the model of the burhani epistemology and how his understanding in his reading of Arabic-reasoning, which he said contained fundamental problems.